Constitutional Implications of Abolishing the Presidential Threshold on Democracy and the Electoral System in Indonesia - Mau, Hedwig Adianto (Universitas Muhammadiyah Ponorogo, 2025)
The Constitutional Court's Decision No. 62/PUU-XXII/2024, which nullified the application of the presidential threshold in Indonesia’s presidential and vice-presidential elections, represents a transformative development in the country's electoral framework. This research investigates the legal and political ramifications of the ruling, particularly its impact on democratic practices and the structure of the electoral system in Indonesia. Employing a normative juridical approach, the study explores the constitutional justification for eliminating the threshold, assesses its effects on political inclusiveness, and examines its implications for governmental stability. The results suggest that eliminating the presidential threshold may strengthen democratic processes by enabling broader candidate participation and encouraging a more competitive political environment. Nevertheless, the absence of such thresholds could also lead to heightened political fragmentation, potentially resulting in a more divided electoral arena. From a regulatory standpoint, this shift demands careful revision of electoral procedures to maintain administrative efficiency and uphold the integrity of election outcomes. This research contributes original insights by being among the first to critically assess the legal reasoning of the Constitutional Court’s decision in the context of Indonesia’s evolving democratic architecture. It highlights the tension between normative constitutional ideals and practical governance needs, offering a nuanced interpretation that bridges theory and institutional realities. However, the study is limited by its focus on normative and doctrinal analysis without incorporating empirical data from political actors or voter behavior post-ruling. In conclusion, the abolition of the presidential threshold introduces a multifaceted impact on Indonesia's democratic development and electoral integrity, warranting further scholarly inquiry into regulatory frameworks that can harmonize openness with governance efficacy post-ruling.